Transcanalicular endoscope combined laser-assisted dacryocystorhinostomy - Pal, Virendra K. (Medknow Publications & Media Pvt Ltd, 2013)
AIMS: In this study, we have tried to assess the success rate and difficulties that we came across while performing the transcanalicular endoscope combined laser-assisted dacryocystorhinostomy (T-ECLAD). MATERIALS AND METHODS: A prospective study of 60 patients suffering from nasolacrimal duct obstruction confirmed by preoperative syringing was carried out at the Regional Institute of Ophthalmology. T-ECLAD is a new minimally invasive dacryocystorhinostomy procedure, which is performed by diode laser (980 nm diode laser with power of 10 watts) through lacrimal canaliculi with the help of a cannula and fiber optic cable. The interior of the nasal cavity was visualized with the help of the nasal endoscope on a monitor. Success of procedure was assessed by patency of the lacrimal drainage system on irrigation. RESULTS: We performed 56 successive T-ECLAD. The average procedure time was 10 min, and on an average 235 Joules of laser energy was needed. We observed a patent nasolacrimal duct on irrigation in 39 out of 56 treated eyes. 1 patient had partial, 5 patients had blocked irrigation, and 10 patients did not return for follow up. This yields a success rate of 69.6% (if we exclude patients who did not return for follow up) with an average follow-up period of 6 months. CONCLUSIONS: The 980-nm T-ECLAD is a new contribution to the field of lacrimal surgery. It is a minimally invasive and quick procedure.